Therapy of Inflammatory Bowel Disease using New 5-ASA Compounds: An Introduction - Ulrich Klotz (Canadian Journal of Gastroenterology)
Strong evidence has been accumulating that mesalazine (5- aminosalicylic acid, 5-ASA) represents the therapeutic moiety of the standard drug sulphasalazine. Since the active metabolite avoids the toxic potential of sulphapyridine, this perception has initiated new therapeutic approaches, for example, two 5-ASA molecules have been coupled to form another prodrug (olsalazine) which again depends on a proper cleavage of the azobond by bacteria in the colon A more direct way has been applied successfully by administering 5-ASA itself in special galenic formulation (suppositories, enemas, controlled release preparations) to provide enough active material at the proposed sites of action in the terminal ileum and/or colon. One major advantage of all 5-ASA compounds, compared to sulphasalazine, is their 10-fold lower potential (incidence) for inducing allergic reactions or causing intolerance. Aside from rare hypersensitivity reactions, 5-ASA can cause nausea. vomiting, headache and gastrointestinal disturbances in 1 to 5% of patients. However, the new azocompound olsalazine induced diarrhea or loose stool in at least 10 to 15% of the treated patients which might limit its use in inflammatory bowel disease (IBD). In conclusion, the ‘old’ metabolite 5-ASA, in a ‘new’ design, offers an effective and very safe choice for the treatment of IBD.